Epidemiological features after emergency declaration in Hokkaido and report of 15 cases of COVID-19 including 3 cases requiring mechanical ventilation - Edagawa, Shunji; Kobayashi, Fumiko; Kodama, Fumihiro; Takada, Masayuki; Itagaki, Yuki; Kodate, Akira; Bando, Keisuke; Sakurai, Keisuke; Endo, Akio; Sageshima, Hisako; Nagasaka, Atsushi (Global Health & Medicine, 2020)
The ongoing spread of coronavirus disease (COVID-19) is a worldwide crisis. Hokkaido Prefecture in Japan promptly declared a state of emergency following the rapid increase of COVID-19 cases, and the policy became an example to mitigate the spread of COVID-19. We herein report 15 cases of COVID-19 including 3 cases requiring mechanical ventilation. Based on review of our cases, among patients over 50 years of age with underlying diseases such as hypertension and diabetes mellitus, and those who required oxygen administration tended to deteriorate. These cases highlight the importance of understanding the background and clinical course of severe cases to predict prognosis.